Pendidikan Seksualitas Perspektif Islam bagi Remaja di IPNU-IPPNU Ranting Desa Loram Wetan Kabupaten Kudus - Farida farida (Konseling Edukasi : Journal of Guidance and Counseling, 2019)
Sexuality Education in Islamic Perspective for Adolescents in IPNU-IPPNU Branch of Loram Wetan Village Kudus Regency. Sexual crime does not only occur between men and women, but also between men, or during childhood, both boys and girls. The existence of sex education in adolescents will make adolescents in IPNU-IPPNU organization able to take care of themselves and socialize to other peers in order to achieve the perfection of human existence in social interaction. The purpose of this study was to find out the efforts to form an understanding of the sex differences between men and women in family, work and throughout life; the role of sex in human and family life, the relationship between sex and love, feelings of sex in marriage and so on; develop self-understanding in relation to sexual functions and needs; and help adolescents to develop their personalities so that they are able to make responsible decisions. This study used qualitative research methods. The results of this research are IPNU-IPPNU adolescent branch of Loram Wetan Village were given information about sex tools based on Islamic values originating from the Qur'an and Hadith, efforts to form an understanding of sex role in human life and so on by providing information about the formation of sakinah family and support from religious figures, sex education is given in a narrow sense (in context), and efforts to help adolescents develop their personalities by supporting all academic and non-academic activities in educational institutions as well as actively participating in IPNU-IPPNU socio-religious activities.Keywords: Education, Sexuality, Adolescents